Napoleon and the Revolution - Jordan, David P. (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2012)
"This new study of Napoleon emphasizes his ties to the French Revolution, his embodiment of its militancy, and his rescue of its legacies. Jordan's work illuminates all aspects of his fabulous career, his views of the Revolution and history, the artists who created and embellished his image, and much of his talk about himself and his achievements"--
HKBU library
YTR2025 M09
Keywords: Napoleon -- Emperor of the French, -- 1769-1821.; HISTORY / Europe / France; HISTORY / Modern / 18th Century; HISTORY / Revolutionary; France -- History -- Revolution, 1789-1799 -- Influence; France -- History -- 1789-1815.